Hungary : 2018 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the headline inflation in Hungary has started to pick up, mainly owing to higher energy prices, while core inflation has been running sideways over the past six months, despite emerging capacity constraints. Unemployment remains on a decreasing trend, and labor shortages are intensifying despite the improvement in participation rates. The 2017 general government fiscal deficit narrowed to 2 percent of GDP, compared with the budgeted 2.4 percent. This outcome was mostly driven by strong GDP growth and reduced interest payments. The IMF staff projects the 2018 overall fiscal deficit at about 2.4 percent of GDP, in line with the budget's target.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet